Pengaruh Variabel Sosial-Lingkungan terhadap Prevalensi Balita Stunting di Pulau Sumatera Tahun 2022 - Amin, Asy-Syaja'ul Haqqul; Marsisno, Waris (Politeknik Statistika STIS, 2024)
Stunting is one of the priority issues addressed by the Indonesian Government. As a region of Western Indonesia, Sumatra Island still has 22 districts/cities with high and very high stunting prevalence status from the results of the 2022 Indonesian Nutritional Status Survey (SSGI). At the same time, the condition of air pollutants in Sumatra also needs to be paid attention to as one of the causes of stunting along with other socio-environmental variables. Therefore, this research aims to determine the influence of socio-environmental variables on the prevalence of stunting in toddlers on the island of Sumatra. The Mixed GWR method was chosen to accommodate spatial heterogeneity in the model so that the results obtained showed that the percentage of women who marry early has an effect on increasing the prevalence of stunting globally. Meanwhile, the percentage of households with access to clean drinking water and the concentration of pollutants in the form of sulfur dioxide and ground-level ozone sourced from satellite imagery data have a local effect in several districts/cities on the island of Sumatra in 2022.